(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2019)
Background: In Calcutta the cheap eating houses which were in abundance 30 years ago have disappeared. The street vendors who sold only raw commodities in the past now sell prepared foods as well. Small shops have been replaced by transportable stands. Street foods are adopted because they are inexpensive, the taste is acceptable and they are conveniently sold wherever people congregate.While the Chinese have been visiting India for millennia in search of Buddhist teachings.As all immigrant communities tend to do, the Chinese assimilated Indian sensibilities and beliefsthe Indian culinary world was affected by a new cuisine. The first Indo Chinese restaurant Eau Chew opened in Kolkata.New restaurants mushroomed all over Kolkata, and legends like Fat Mama and Kim Fa were born, offering newer dishes with fancier combinations and names. Before you knew it “Indian Chinese” had tickled the taste buds of folk in every small town and city.The Chinese food served in India is extensively Indianized, and there are certain Indian expectations of what Chinese food is. Objective: The main focus of research is on the Chinese food prevalence and its acceptability to Chinese food palatable to Indian pallet. Methodology: A quantative research was done on the basis of random sampling.Random sampling was done for Chinese immigrants and local historians. The total no. of respondents was (n=100) between age 20 to 80 years.Results: After the analysis of the results it was discovered that the prevalence and acceptance of Chinese food in Kolkata still exists strongly and the demand for it still continues among the local people and historians as well. Conclusion:The authentic Chinese foods still remain strange to the Indian people. The intrinsically Indian-Chinese food claims the position of Chinese food in India, and it is popular and widely accepted as Chinese food.